До характеристики завдань та функцій керівника територіального управління Державного бюро розслідувань - Курепін, Р. Ю.; Kurepin, R. Yu. (Європейські перспективи. - 2022. - № 4. - С. 255-260, 2022)
У статті, спираючись на аналіз наукових поглядів вчених, розкрито теоретичні підходи щодо визначення понять завдань та функцій в контексті діяльності керівника територіального управління Державного бюро розслідувань. Виокремлено перелік завдань керівників управлінь ДБР, на основі чого акцентовано увагу, що вони лежать в основі формування функцій, які виконують відповідні суб’єкти. Визначено, що функції керівника – це обумовлені його завданнями напрямки діяльності, спрямовані на задоволення тих потреб територіального управління ДБР, які є необхідними для його належної роботи. Функції змістовно проявляються при реалізації визначеної законодавством компетенції та повноважень керівника. До загально-управлінських функцій, які набувають специфічного змісту в діяльності розглядуваних керівників, запропоновано віднести: представницьку, матеріально-забезпечувальну, організаційну, кадрову, дисциплінарну та інші.

It is argued that the direct list of tasks of the head of the territorial administration is not singled out by the legislator. Such tasks can be distinguished from the content of the programs and reports that he must prepare annually. The following are the key tasks of the head of the territorial department of the SBI: 1) ensuring the proper recording of statements and reports about criminal offenses, as well as their disclosure and investigation (observance of the legislation on the conduct of operational, investigative and investigative activities); 2) overcoming the consequences of committing criminal offenses subject to investigation by the territorial administration, by bringing the guilty to responsibility and returning the illegally obtained funds when they were committed; 3) creation of conditions for proper and effective interaction with entities necessary to fulfill the goals of management activities; 4) ensuring international and public cooperation; 5) support by employees of the required level of professional skill and compliance with official discipline; 6) rational use of financial and material resources of territorial management, etc. It was determined that the manager’s functions are the areas of activity determined by his tasks, aimed at meeting the needs of the territorial management of the SBI, which are necessary for his proper work. The functions are meaningfully manifested in the implementation of the competence and powers of the manager defined by the law. It is proposed to include general management functions that acquire a specific meaning in the activities of the managers in question: representative, material and support, organizational, personnel, disciplinary and other.

В статье, опираясь на анализ научных взглядов ученых, раскрыты теоретические подходы к определению понятий задач и функций в контексте деятельности руководителя территориального управления Государственного бюро расследований. Выделен перечень задач руководителей управлений ГБР, на основе которых акцентировано внимание, что они лежат в основе формирования функций, выполняющих соответствующие субъекты. Определено, что функции руководителя – это обусловленные его задачами направления деятельности, направленные на удовлетворение этих потребностей территориального управления ГБР, которые необходимы для его надлежащей работы.
Keywords: Державне бюро розслідувань; територіальне управління; керівник; завдання; функції; State Bureau of Investigation; territorial administration; head; tasks; functions; Государственное бюро расследований; территориальное управление; руководитель; задачи; функции